2013
DOI: 10.3109/02656736.2013.798037
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Hsp70 inhibits pro-inflammatory cytokine production by IL-10 driven down-regulation of C/EBPβ and C/EBPδ

Abstract: C/EBPβ and C/EBPδ transcription factors are inhibited by Hsp70 treatment, and their inhibition occurs via the TLR2-ERK-STAT3-IL-10 pathway in BMDCs, mediating the anti-inflammatory effects of Hsp70.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 62 publications
1
27
1
Order By: Relevance
“…Glutamine ¼ glutamine, LPS ¼ endotoxin *p < 0.05, **p < 0.005. model of sepsis model using, either lipoteichoic acid or LPS, shows that pre-treatment of human neutrophils with recombinant HSP70 prior to the administration of endotoxin attenuates the release of TNF-a [41]. This is corroborated in other in vitro animal models where the use of recombinant HSP70 provides a similar antiinflammatory mode of action by inhibiting C/EBPb and C/EPBd transcription factors from signalling via TLR2-ERK-STAT2-1L10 pathway, attenuating the release of pro-inflammatory mediators [42]. Converse to this, when healthy subjects were inoculated with endotoxin, levels of HSP70 and proinflammatory mediators …”
Section: Discussionsupporting
confidence: 60%
“…Glutamine ¼ glutamine, LPS ¼ endotoxin *p < 0.05, **p < 0.005. model of sepsis model using, either lipoteichoic acid or LPS, shows that pre-treatment of human neutrophils with recombinant HSP70 prior to the administration of endotoxin attenuates the release of TNF-a [41]. This is corroborated in other in vitro animal models where the use of recombinant HSP70 provides a similar antiinflammatory mode of action by inhibiting C/EBPb and C/EPBd transcription factors from signalling via TLR2-ERK-STAT2-1L10 pathway, attenuating the release of pro-inflammatory mediators [42]. Converse to this, when healthy subjects were inoculated with endotoxin, levels of HSP70 and proinflammatory mediators …”
Section: Discussionsupporting
confidence: 60%
“…DnaK can induce the production of IL-10 in dendritic cells [14], macrophages [10], and synovial cells from arthritis patients [33]. Moreover, in M. tuberculosis (Mtb) DnaK can modulate the production of pro-inflammatory cytokines via IL-10 in murine dendritic cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic modulation of cytokine expression offers the possibility of major changes in adipose tissue physiology. Adipocytes can synthesize some inflammatory cytokines such as interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and interleukin-1beta (IL-1β) (Coppack 2001;Kern et al 2001;Wu et al 2007), and possible relationships between Hsp70 and inflammatory cytokine expression were observed in some studies (Asea et al 2000;Borges et al 2013;Van Molle et al 2002). It was also reported that restraint stress induced Hsp70 in adipose tissue (Yamamoto et al 2002).…”
Section: Introductionmentioning
confidence: 99%